2014
DOI: 10.1038/gt.2014.91
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive, neuron-specific gene therapy can be facilitated by focused ultrasound and recombinant adeno-associated virus

Abstract: Recombinant adeno-associated virus (rAAV) has shown great promise as a potential cure for neurodegenerative diseases. The existence of the blood-brain barrier (BBB), however, hinders efficient delivery of the viral vectors. Direct infusion through craniotomy is the most commonly used approach to achieve rAAV delivery, which carries increased risks of infection and other complications. Here we report a focused ultrasound (FUS) facilitated, non-invasive rAAV delivery paradigm that is capable of producing targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 32 publications
2
98
0
Order By: Relevance
“…Use of pressurized convection-enhanced delivery (CED) and magnetic resonance imaging (MRI)-guided infusion can lead to significantly better distribution compared to single injections of smaller volumes (Bankiewicz et al, 2000). Facilitated access across the BBB with AAV has also been achieved using focused ultrasound and microbubbles (Wang et al, 2015). …”
Section: Deliver the Vector The More The Better (Modes And Sites mentioning
confidence: 99%
“…Use of pressurized convection-enhanced delivery (CED) and magnetic resonance imaging (MRI)-guided infusion can lead to significantly better distribution compared to single injections of smaller volumes (Bankiewicz et al, 2000). Facilitated access across the BBB with AAV has also been achieved using focused ultrasound and microbubbles (Wang et al, 2015). …”
Section: Deliver the Vector The More The Better (Modes And Sites mentioning
confidence: 99%
“…Indeed, the delivery of chemotherapeutic drugs (Escoffre et al 2013; Kang et al 2010; Kotopoulis et al 2013; Tinkov et al 2010), DNA (Carson et al 2011; Christiansen et al 2003) and siRNA (Carson et al 2012; Kinoshita and Hynynen 2005) has been shown in both in vitro and in vivo contexts. In addition to these applications, studies have shown that ultrasound stimulated microbubbles can transiently and locally disrupt the blood brain barrier (BBB) in order to facilitate drug delivery for the treatment of brain disorders (Park et al 2012; Tung et al 2011; Wang et al 2015; Weber-Adrian et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…BBBD, the subject of the current study, reversibly opens the blood-brain barrier (BBB) enabling the delivery of even large-molecule therapeutics to the central nervous system and offers great potential for treating multiple neurological disorders. This technology has been demonstrated in rodent (11)(12)(13)(14)(15)(16) and nonhuman primate (17,18) models, and clinical trials are underway (19,20).…”
mentioning
confidence: 99%